Senses of Home in the Field - Gold, Daniel (Fieldwork in religion, 2020)
The author identifies different senses of home sometimes experienced by fieldworkers and the kinds of places that nurture them. In addition to the sense of fieldworkers being in their own cul-tural environment, a baseline never fully attained in the field, the author identifies a fieldworker's retreat, where he or she can be alone at their fieldsite and relax without worrying about others' cultural expectations; the possible alternative home especially available to those doing multi-sited research, a place away from any fieldsite that may also offer the camaraderie of casual friends; and, finally, the fieldsite as second home, where the empathetic fieldworker develops lasting affective ties to those among whom he or she lives. Some implications of these different senses of home are discussed as the author has experienced them over many long and short visits to North India beginning in the late 1960s.